1993
DOI: 10.1007/bf01378648
|View full text |Cite
|
Sign up to set email alerts
|

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence

Abstract: Hog cholera virus antigens were found densely distributed in skin and tongue of pigs experimentally infected with hog cholera virus. The finding described here warrants the usage of ear biopsies for hog cholera diagnosis on a herd basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
(2 reference statements)
2
4
1
Order By: Relevance
“…6 Viral infection has been described in neurons, glial cells, endothelial cells, and CNS cell infiltrate during CSF. 18, 28 A similar viral antigen distribution has recently been reported in a calf with BVD virus type II infection. 2…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…6 Viral infection has been described in neurons, glial cells, endothelial cells, and CNS cell infiltrate during CSF. 18, 28 A similar viral antigen distribution has recently been reported in a calf with BVD virus type II infection. 2…”
Section: Introductionsupporting
confidence: 74%
“…6 Viral infection has been described in neurons, glial cells, endothelial cells, and CNS cell infiltrate during CSF. 18,28 A similar viral antigen distribution has recently been reported in a calf with BVD virus type II infection. 2 This paper reports on a study designed to chart the spatial and chronologic distribution of lesions and virus antigen in the CNS, and to characterize cellular infiltrate and infected cells, to learn more about the pathogenesis of CSF-induced lesions of the CNS and determine the exact role of the virus in these lesions.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Nervous tissue is considered as one of the target tissues for CSFV, and histological lesions in the brains of pigs with chronic CSFV infection are similar to those in pigs experimentally inoculated with a low-virulence CSFV strain (Choi and Chae, 2003). Previous studies reported viral antigen detection in neurons, glial cells, endothelial cells, and cell infi ltrate during CSF infection (Pan et al, 1993;De las Mulas et al, 1997;Gómez-Villamandos et al, 2006;Polaček et al, 2008). A similar viral antigen distribution has been detected in our study, with the main exception of IHC positive neurons, although infection of neurons is reported in natural outbreaks of CSF (Pan et al, 1993;Trautwein, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported viral antigen detection in neurons, glial cells, endothelial cells, and cell infi ltrate during CSF infection (Pan et al, 1993;De las Mulas et al, 1997;Gómez-Villamandos et al, 2006;Polaček et al, 2008). A similar viral antigen distribution has been detected in our study, with the main exception of IHC positive neurons, although infection of neurons is reported in natural outbreaks of CSF (Pan et al, 1993;Trautwein, 1988). Th is diff erence may be due to a more prolonged course of the natural infection studied in mature pigs.…”
Section: Discussionmentioning
confidence: 98%